Morphological expression and histological analysis of imposex in Gemophos viverratus (Kiener, 1834) (Gastropoda: Buccinidae): a new bioindicator of tributyltin pollution on the West African coast - Lopes-Dos-Santos, Ruy M. A.
We describe the reproductive system and morphological expression of imposex in the marine gastropod Gemophos viverratus (Kiener, 1834) for the first time. This species can be used as a bioindicator of tributyltin (TBT) pollution on the west coast of Africa, a region for which there is a lack of information regarding levels and impacts of TBT pollution. Adult G. viverratus were collected between August 2012 and July 2013 in Sao Vicente Island (Republic of Cabo Verde), at pristine sites on the northeastern and eastern coasts and at Porto Grande Bay, the major harbour in the country. All the females (n = 81) caught outside the bay were normal, but 99% (n = 108) of those collected inside the bay exhibited degrees of abnormal virilization. Seven levels of imposex intensity, from stage 0 (normal) to stage 6 (sterilized females), are described following at least three different pathways of evolution (a, b and c). Female sterilization was caused mainly by abnormal growth of 'tumour-like' tissues in the oviduct. A peculiar characteristic of imposex in this species is the development of a distal prostate by females, resembling the same organ exhibited by males. In the laboratory, imposex could be artificially induced by injecting very small doses of TBT into females, demonstrating that TBT is a causative agent of this syndrome.